Ruminal fatty acid outflow in dry cows fed different sources of linoleic acid: reticulum and omasum as alternative sampling sites to abomasum - Freitas Júnior, José E.; Bettero, Vitor P. [UNESP]; Zanferari, Filipe; Del Valle, Tiago A.; De Paiva, Pablo G. [UNESP]; Ferreira De Jesus, Elmeson [UNESP]; Takiya, Caio S.; Leite, Laudi C.; Dias, Márcia; Rennó, Francisco P. (Taylor & Francis, 2019)
This study was designed to determine the rumen outflow of fatty acids (FA) and biohydrogenation (BH) extent using alternative sampling sites (reticulum and omasum) to abomasum in dry cows fed different sources of FA. Four Holstein non-pregnant dry cows (≥3 parturitions, and 712 ± 125 kg BW), cannulated in the rumen and abomasum, were randomly assigned to a 4 × 4 Latin square design experiment, containing the following treatments: 1) control (CON); 2) soya bean oil (SO), dietary inclusion at 30 g/kg; 3) whole raw soya beans (WS), dietary inclusion at 160 g/kg; and 4) calcium salts of FA (CSFA), dietary inclusion at 32 g/kg. Rumen outflow of nutrients was estimated using the three markers reconstitution system (cobalt-EDTA, ytterbium chloride, and indigestible neutral detergent fibre [NDF]). Diets with FA sources decreased feed intake and increased FA intake. No differences in nutrient intake and digestibility were detected among cows fed diets supplemented with different FA sources. Diets with FA sources reduced the rumen outflow of DM and NDF, hence decreasing their passage rates. In addition, SO diet reduced the ruminal outflow of DM and NDF in comparison with WS and CSFA. Omasal sampling yielded the highest values of rumen outflow of NDF and potentially degradable NDF (pdNDF), whereas the reticular and abomasal samplings yielded intermediate and least values, respectively. The interaction effect between diet and sampling site was observed for rumen outflow of majority FA (except for C16:0, C18:0, and C18:2 trans-10, cis-12) and BH extension of C18:1 cis, C18:2, and C18:3. Calculations derived from abomasal sampling revealed that WS and CSFA diets had lower BH extent of C18:1 cis and C18:2 in comparison with SO, whereas cows fed CSFA had greater BH extent of C18:3 and lower BH extent of C18:1 cis compared to those fed WS. However, the latter results were not similar when calculations were performed based on the reticular and omasal samplings. Thus, there is evidence that neither reticular nor omasal samplings are suitable for estimating rumen outflow of FA in dry cows. In addition, WS and CSFA diets can increase the abomasal flow of polyunsaturated FA in dry cows.
Keywords: Calcium salts; cows; fatty acids; post-ruminal flow; sampling technique; whole raw soya bean